Reformulation Of The Law On Information And Electronic Transactions In The Enforcement Of Criminal Acts Related To Fake News Through Social Media - Fahrul Anggara Putra; Lomba Sultan; Abdul Wahid Haddade; Munadi (CBJIS: Cross-Border Journal of Islamic Studies, 2025)
The rapid development of information and communication technology has had a significant impact on society, particularly through the use of social media as the primary means of disseminating information. However, this convenience has also triggered serious problems related to the spread of fake news (hoaxes), which can cause public unrest and even have implications for social and legal stability. This study aims to analyze the enforcement of laws against the criminal act of spreading fake news through social media, examine the urgency of the Electronic Information and Transactions Law (EIT Law), and formulate alternatives for reformulating Article 28(1) of the EIT Law to make it clearer and more applicable. The method used is a normative legal approach with qualitative analysis, supported by case studies and observations of the implementation of the law by the Cyber Crime Unit of the West Kalimantan Regional Police, as well as an examination of the Joint Ministerial Decree of 2021. The results of the study indicate that law enforcement against hoaxes still faces challenges in terms of proving legal elements and the ambiguity of the wording of the norms in the ITE Law. Additionally, the urgency for regulatory updates is high, as the improper application of certain provisions in some cases has led to potential violations of the right to freedom of expression. Therefore, a reformulation of Article 28(1) is necessary, emphasizing objective terminological boundaries and the actual impact of false information. This reformulation is expected to provide legal clarity, enhance enforcement effectiveness, and ensure the protection of civil liberties in the digital age.